The Effect of Work Culture, Discipline, Training, Work Facilities, and Welfare on the Job Performance of Civil Servants at the Lahat Regency Public Order Agency - Destya Dwi Lestari; Abdul Hamid; Nisma Aprini (Social Sciences Journal, 2026)
This study aims to determine the effect of Work Culture, Discipline, Training, Work Facilities and Welfare on the Work Performance of Civil Servants at the Lahat Regency Civil Service Police Unit. The sampling method used is Incidental sampling. In this study, the research sample was all employees who have the status of civil servants at the Lahat Regency Civil Service Police Unit, totaling 44 people. Instrument validity testing used person's product moment correlation, while reliability testing used Alpha Cronbach. Data analysis used multiple regression analysis. The results of the analysis show that: 1). There is a positive and significant influence between work culture on work performance of t count 3.933 with a significance value of 0.000 <0.05. 2) there is a positive and significant influence between discipline on work performance with t count 3.312 with a significance value of 0.002 <0.05. 3) there is no positive and insignificant effect between training on work performance with t count 1.722 with a significant value of 0.093 > 0.05. 4) There is a positive and significant effect between work facilities on work performance of t count 2.965 with a significant value of 0.005 < 0.05. 5) There is a negative and insignificant effect between welfare on work performance of t count -1.988 with a significant value of 0.064 > 0.05. 5) There is a significant positive effect between the variables of Work Culture, Discipline, Training, Work Facilities and Welfare on the Work Performance of Civil Servants at the Lahat Regency Civil Service Police Unit with a calculated F value of 7.370; a significant value of 0.000 < 0.05.